High-pressure veins in corona gabbros of Khwaza Khela, Kohistan - Jan, M. Qasim; Karim, Ajaz (Journal of Himalayan Earth Sciences, 1992)
Gabbroic rocks of Khwaza Khela in the southern amphibolite belt of the Kohistan island arc preserve a record of thermal history from magmatic crystallization to high-pressure vein formation. The rocks formed from arc-related magma at about 1000 oC, 3-4kb, probably during the Early Cretaceous. Subsequently calcic plagioclase and olivine reacted to form orthopyroxene + clinopyroxene + spinel ± tschermakite coronas at -800 oC, 6-8kb. The corona formation may have occurred in the early stages of the closure of the arc with the Karakoram plate (-95-102 Ma ago). Finally, the rocks were subjected to high-pressure metamorphism which is reflected in thin quartzofeldspathic veins containing garnet, zoisite, paragonite and kyanite were formed at 500-600 oC, 10-12kb. This paper presents petrography of these rocks and discusses the tectonic implications of the coronas and high-pressure veins which developed in response to cooling and crustal thickening.